2016
DOI: 10.1093/aje/kww110
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Influenza Immunization and Adverse Birth Outcomes: Using Data and Practice to Inform Theory and Research Design

Abstract: Maternal influenza immunization can reduce influenza-attributable morbidity and mortality among pregnant women and infants who are too young to be vaccinated. Data from empirical studies also support the hypothesis that immunization can protect the fetus against adverse outcomes if the mother is exposed to influenza. In their theoretical analysis in the Journal, Hutcheon et al. (Am J Epidemiol. 2016;184(3):227–232) critiqued the existing evidence of the fetal benefits of maternal influenza immunization by calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We noted above (and again below) that the evidence for a role of microbes in pre-term birth (PTB) is overwhelming (also reviewed in [32]). From an immunological point of view, there seems to be a hugely beneficial outcome of vaccination against influenza in terms of lowering pre-term birth [573][574][575][576][577][578] (cf. [579]) or stillbirth [580].…”
Section: Effects Of Vaccination On Pregnancy Outcomes Including Pre-mentioning
confidence: 99%
“…We noted above (and again below) that the evidence for a role of microbes in pre-term birth (PTB) is overwhelming (also reviewed in [32]). From an immunological point of view, there seems to be a hugely beneficial outcome of vaccination against influenza in terms of lowering pre-term birth [573][574][575][576][577][578] (cf. [579]) or stillbirth [580].…”
Section: Effects Of Vaccination On Pregnancy Outcomes Including Pre-mentioning
confidence: 99%
“…We appreciate the opportunity to address the concerns of Phadke et al (1) regarding our recent article (2). First, we agree that accounting for the time-dependent nature of influenza illness, immunization, and pregnancy outcomes is critical for obtaining unbiased estimates of the association between maternal influenza immunization and fetal health (3).…”
mentioning
confidence: 94%
“…That claim is not supported by the conclusions of the cited paper, however, in which the authors state that they “found a strong protective effect of vaccination on preterm birth (relative risk: 0.79; 95% [confidence interval]: 0.74, 0.85) when ignoring potential biases and no effect when accounting for them (relative risk: 0.91; 95% [confidence interval]: 0.83, 1.0)” (13, p. 176). Likewise, of the 4 studies used to support the claim that “[e]mpirical studies with analyses of birth outcomes stratified by period of influenza circulation have yielded remarkably consistent findings” (1, p. 789), 2 (from the same population) are highly prone to immortal time bias due to their use of a time-fixed exposure variable (immunization at any point in pregnancy (ever vs. never)) (14, 15), and the third reported null associations between maternal immunization and fetal outcomes (for preterm birth, adjusted hazard ratio = 1.03, 95% confidence interval: 0.84, 1.25; for fetal death, adjusted hazard ratio = 0.88, 95% confidence interval: 0.66, 1.17) (16). In the absence of consistent, high-quality evidence of fetal benefits from maternal influenza immunization and with practical constraints on the detection of such benefits, we believe that immunization policies should be based on the strong evidence that immunization protects both mothers and their infants against influenza illness (5, 6, 17).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…[26][27][28] With respect to influenza immunization, for example, studies have shown a reduction in influenza-related adverse outcomes such as hospital admissions, mother and infant mortality, and illness severity. 29,30 Fetuses acquire antibody protection in utero via maternal immunization, as well as at the post-partum stage ( 6 months) wherein antibodies are transferred through breastfeeding; study outcomes reflect greater birth weight among infants of mothers who received maternal immunization, as well as influenza disease protection, and moderately favorable nutritional status difference compared to non-immunized women. [31][32][33][34] Recent evidence has suggested that vaccine education during pregnancy will boost future uptake of infant vaccines.…”
Section: Introductionmentioning
confidence: 99%